PENGARUH KARAKTERISTIK PEKERJAAN DAN GAYA KEPEMIMPINAN TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL DAN KEPUASAN KERJA - 11.5.202.0103, Kartini Endah Purwaningsih (Jurnal Mahasiswa Pasca Sarjana, 2013)
Purpose of this study is to examine and analyze the effect of job characteristics , leadership styles on performance by mediating organizational commitment and job satisfaction ( a study at the Department of Agriculture , Agriculture and Forestry and the Department of Animal Husbandry and Fisheries Waterford County ) .Total sample number of 107 people . Primary data were obtained using a questionnaire developed from the indicator variable job characteristics , leadership styles on employee performance with the mediation of organizational commitment and job satisfaction . Top scores on the questionnaire using a Likert scale of 1 to 7 continuum . Methods of data using multiple regression analysis .Job Characteristics hypothesis testing results and did not have a significant negative impact on Organizational Commitment , Leadership Style has a positive and significant impact on Organizational Commitment , Job Characteristics and did not have a significant negative effect on Job Satisfaction , Leadership Style and Organizational Commitment has a positive and significant impact on satisfaction work, employment and Characteristics of Leadership Style has a positive and significant effect on Employee Performance and Organizational Commitment and Job Satisfaction has a positive and significant influence on employee performance. Key words : Job Characteristics, Leadership Style, Organizational Commitment, Job Satisfaction and Performance